DISTRIBUTED RESTful WEB SERVICES FOR RECONSTRUCTION AND ANALYSIS OF GENE NETWORKS - N. L. Podkolodnyy; A. V. Semenychev; D. A. Rasskazov; V. G. Borowsky; E. A. Ananko; E. V. Ignatieva; N. N. Podkolodnaya; O. A. Podkolodnaya; N. A. Kolchanov (Вавиловский журнал генетики и селекции)
This paper describes a RESTful Web service-based distributed software system, which focuses on the reconstruction of gene networks by integrating data from heterogeneous data sources, including databases of molecular-genetic interactions, metabolic and signaling pathways, gene networks, etc.